Clinical evaluation of coronally advanced flap with or without a platelet-rich fibrin membrane for the root coverage - Rajeev K Jaiswal; Deepti Chandra; Md Arif Khan; Sanjay Gupta; Piyush Gowrav; Surendra Kumar Yadav (Wolters Kluwer Medknow Publications, 2024)
Aim: To evaluate "coronally advanced flap" with or without "a platelet-rich fibrin membrane for the root coverage." Materials and Methods: All the clinical parameters were assessed at different time intervals (at baseline, 1, 3, and 6 months) in both experimental and control group. Following "clinical parameters" were recorded using "UNC-15" "Probe-Plaque Index (PI)" (Silness and Loe, 1964), "Gingival Index" (GI) (Loe and Silness, 1963), "Recession depth (RD)," "Recession width (RW)," "Clinical attachment level (CAL)," and "Width of keratinized gingiva (WKG)". Results: At final evaluation (i.e., mean change from baseline to 6 months), "the decrease in Plaque Index was 2.5% higher in Group B (66.0%) as compared to Group A (63.5%). The decrease in Gingival Index was 6.1% higher in Group B (91.4%) as compared to Group A (85.3%), and the decrease in recession width was 4.0% higher in Group B (75.2%) as compared to Group A (71.2%). The decrease in clinical attachment level was 4.4% higher in Group B (53.2%) as compared to Group A (48.4%). The increase in width of keratinized gingiva was 1.9% higher in Group A (28.8%) as compared to Group B (26.9%)." Conclusion: The controlled, randomized, split mouth design showed that CAF surgery, either by alone or in combination with PRF, is an efficient treatment method for covering denuded roots. "This design was used to treat bilateral isolated Miller's class I and II recessions in gingival part. When compared to the CAF approach, the results from a combination of CAF and PRF after a 6-month period showed additional advantages in addition to mean root coverage in the treatment of Miller's classes I and II recessions in gingival part."